Comparative Insight of Regulatory Guidelines for Probiotics in USA, India and Malaysia: A Critical Review - Arora, Malika; Sharma, Sujata; Baldi, Ashish (International Journal of Biotechnology for Wellness Industries, 2013)
Probiotics have always been a unique category of natural products due to established evidences of their applications in wellness of human beings. Inspite of being based on live microorganisms, commercial exploration of probiotics as biologics, pharmaceuticals, food and nutritional supplements has witnessed a tremendous increase due to their potential of providing health benefits. Currently different regulatory bodies across the globe consider probiotics under several categories depending upon their intended use. In order to clear the ambiguity related to regulatory specifications, assurance of quality and premarketing safety assessment for drafting of comprehensive guidelines with global acceptance is need of the hour. The aim of this paper is to compare existing regulations in countries like United States, India and Malaysia to develop harmonized guidelines for approval of probiotics.